Proceedings of the 33rd Annual ACM/IEEE Symposium on Logic in Computer Science 2018
DOI: 10.1145/3209108.3209123
|View full text |Cite
|
Sign up to set email alerts
|

Logical paradoxes in quantum computation

Abstract: The precise features of quantum theory enabling quantum computational power are unclear. Contextuality-the denial of a notion of classical physical reality-has emerged as a promising hypothesis: e.g. Howard et al. showed that the magic states needed to practically achieve quantum computation are contextual.Strong contextuality, as defined by Abramsky-Brandenburger, is an extremal form of contextuality describing systems that exhibit logically paradoxical behaviour.After introducing number-theoretic techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…It has been argued that contextuality is a resource for quantum computation. In particular, for the quantum computing architecture known as measurement-based quantum computation (MBQC) it has been shown that contextuality allows to outperform certain non-contextual settings [5,51,19,30]. Furthermore, in [36] it is proven that contextuality is essential also for magic state injection in the stabiliser formalism.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that contextuality is a resource for quantum computation. In particular, for the quantum computing architecture known as measurement-based quantum computation (MBQC) it has been shown that contextuality allows to outperform certain non-contextual settings [5,51,19,30]. Furthermore, in [36] it is proven that contextuality is essential also for magic state injection in the stabiliser formalism.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, it will be shown that subsets of projectors within the IC-POVMs below may sometimes be used to derive proofs of KS theorem (in Dimensions 4, 8 and 9). Contextuality and negativity of the Wigner function happen to play a fundamental role in universal schemes of quantum computation (e.g., [ 10 , 20 , 30 , 31 ]).…”
Section: Prolegomenon About and Its Relation To Ic-povmentioning
confidence: 99%
“…In 2011, Abramsky & Brandenburger introduced an abstract mathematical framework based on sheaf theory to describe these phenomena in a unified treatment, thereby providing a common general theory for the study of non-locality and contextuality, which had been carried out in a rather concrete, example-driven fashion until then [3]. This high-level description shows that contextuality is not a feature specific to quantum theory, but rather a general Notable examples of the sheaf-theoretic notion of contextuality have been found in connection with relational database theory [4], robust constraint satisfaction [5], natural language semantics [6] and logical paradoxes [7][8][9]. This profusion of instances motivates the search for a general theory of contextual semantics, an all-comprehensive approach able to capture the essence and structure of contextual behaviour.…”
Section: Introductionmentioning
confidence: 98%
“…All rights reserved. Notable examples of the sheaf-theoretic notion of contextuality have been found in connection with relational database theory [4], robust constraint satisfaction [5], natural language semantics [6] and logical paradoxes [7][8][9]. This profusion of instances motivates the search for a general theory of contextual semantics, an all-comprehensive approach able to capture the essence and structure of contextual behaviour.…”
Section: Introductionmentioning
confidence: 99%